2015
DOI: 10.1002/asia.201500913
|View full text |Cite
|
Sign up to set email alerts
|

HepG2 Cell Resistance against Camptothecin from a Lysosomal Drug Delivery

Abstract: A galactose-appended drug delivery system released camptothecin (CPT) to lysosomes of HepG2 hepatoma cells, resulting in the cell resistance to the anticancer drug. We found that the resistance to CPT is caused by alteration of the drug release from the prodrug in lysosomes, emphasizing that the final delivery locations may critically influence drug efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Another possible reason for not observing any effect of fructose exposure on CS activity could be due to the type of in vitro model used in the study (L6 versus HepG2 cells). L6 myotubes are mouse cells, whereas HepG2 cells are human liver carcinoma cells that have a tendency to be resistant to a variety of stimuli [15,16], and they have an upregulated carbohydrate metabolism [17,18]. To this end, another study has shown that in a model of HepG2 mitochondrial dysfunction, CS activity remained unaltered despite the presence of a pathophysiologic stimulus [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason for not observing any effect of fructose exposure on CS activity could be due to the type of in vitro model used in the study (L6 versus HepG2 cells). L6 myotubes are mouse cells, whereas HepG2 cells are human liver carcinoma cells that have a tendency to be resistant to a variety of stimuli [15,16], and they have an upregulated carbohydrate metabolism [17,18]. To this end, another study has shown that in a model of HepG2 mitochondrial dysfunction, CS activity remained unaltered despite the presence of a pathophysiologic stimulus [19].…”
Section: Discussionmentioning
confidence: 99%